2004
DOI: 10.1080/01431160310001603592
|View full text |Cite
|
Sign up to set email alerts
|

Becoming a manual occupation? The construction of a therapy manual for use with language impaired children in mainstream primary schools

Abstract: The construction and use of a therapy manual allowed the provision of replicable therapy within the research project whilst maintaining flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…The intervention was designed along dimensions previously identified for manual-guided treatment, [29] drew together procedures for language intervention considered by researcher and professionals likely to be effective, [30] and was well-received by children, schools and parents.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention was designed along dimensions previously identified for manual-guided treatment, [29] drew together procedures for language intervention considered by researcher and professionals likely to be effective, [30] and was well-received by children, schools and parents.…”
Section: Introductionmentioning
confidence: 99%
“…There are few controlled studies of the efficacy of treatment for children with speech and language delay (Law et al 2004). A search of the four major databases relevant to the study ( Medline , PsyInfo , ERIC , and Linguistics and Language Behaviour Abstracts ) and of unpublished research was carried out and identified five controlled studies providing evidence of the efficacy of both direct and indirect and group and individual approaches to intervention within the 6–11 years age range (for details, see McCartney et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been no direct comparisons between these therapy modes and although there is evidence indicating that direct and indirect approaches to therapy yield comparable outcomes for expressive language (McCartney et al 2004), there is a dearth of data regarding outcomes for other areas of language within the 6–11 years age group, most notably receptive language.…”
Section: Introductionmentioning
confidence: 99%
“…For example, at home, parents often ask children to tell personal stories about experiences they have had, and children listen to and read narratives as part of their language arts instruction at school (Geist & Aldridge, 2002;Jordan, Snow, & Porche, 2000;Riding & Tite, 1985). Narrative intervention is often incorporated into treatment plans because of its functional nature and its relationship to academic demands (Davies, Shanks, & Davies, 2004;Gillam, McFadden, & van Kleeck, 1995;Hayward & Schneider, 2000;McCartney et al, 2004;McFadden, 1998;Peterson, Jesso, & McCabe, 1999;Schoenbrodt, Kerins, & Gesell, 2003;Stiegler & Hoffman, 2001;Ukrainetz, 1998). While current publications provide anecdotal evidence and guidelines for the dynamic assessment of narratives (Gillam & McFadden, 1994;Gillam et al, 1999;Gutierrez-Clellen, Peña, & Quinn, 1995;Gutierrez-Clellen & Quinn, 1993; Iglesias, 1985; Iglesias & GutierrezClellen, 1988;L.…”
Section: Conclusion-mentioning
confidence: 99%